ANALISIS KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR PADA MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) DENGAN METODE FLIPPED LEARNING BERBANTUAN GOOGLE CLASSROOM - Khardita, Deby; Isnarto; Asih, Tri Sri Noor; Agoestanto, Arief (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This study aims to analyze the quality of mathematics learning after applying the Student Facilitator Explaining Learning Model with the Google Classroom-Assisted Flipped Learning Method on mathematical reasoning abilities in terms of student learning independence. The data collection techniques used are test methods, documentation, questionnaires, and observations. The research instruments used are mathematical reasoning ability test questions, liket scales of learning independence, observation sheets and learning implementation. In this study, quantitative research methods with purposive sampling technique research samples and obtained VII A as an experimental class and VII B as a control class. With the results of research (1) quality Google Classroom-assisted SFE learning on students' mathematical reasoning abilities (2) There is a strong influence of student learning independence on mathematical reasoning abilities in the Student Facilitator and Explaining learning model Assisted by Google Classroom.